CLINICAL ENDPOINTS FOR THE STUDY OF GEOGRAPHIC ATROPHY SECONDARY TO AGE-RELATED MACULAR DEGENERATION. Issue 10 (October 2016) - Sadda, SriniVas R.; Chakravarthy, Usha; Birch, David G.; Staurenghi, Giovanni; Henry, Erin C.; Brittain, Christopher
Abstract : Purpose: To summarize the recent literature describing the application of modern technologies in the study of patients with geographic atrophy (GA) secondary to age-related macular degeneration. Methods: Review of the literature describing the terms and definitions used to describe GA, imaging modalities used to capture and measure GA, and the tests of visual function and functional deficits that occur in patients with GA. Results: In this paper, we describe the evolution of the definitions used to describe GA. We compare imaging modalities used in the characterization of GA, report on the sensitivity and specificity of the techniques where data exist, and describe the correlations between these various modes of capturing the presence of GA. We review the functional tests that have been used in patients with GA, and critically examine their ability to detect and quantify visual deficits. Conclusion: Ophthalmologists and retina specialists now have a wide range of assessments available for the functional and anatomic characterization of GA in patients with age-related macular degeneration. To date, studies have been limited by their unimodal approach, and we recommend that future studies of GA use multimodal imaging. We also suggest strategies for the optimal functional testing of patients with GA. Abstract : Ophthalmologists and retina specialists now have a wide range of functional and anatomic assessments available for the characterization of geographic atrophy in patients with age-related macular degeneration. This review summarizes the recent literature describing the application of modern techniques for the study of geographic atrophy.